Topical issues in the study of grief after the loss of a loved one - Лещук, Ірина; But Тетяна (Psychosomatic Medicine and General Practice, 2024)
Abstract. Wars and armed conflicts are usually accompanied by a large number of losses. Grief in most cases is an adaptive process, during which a person experiencing a loss adjusts to the realities of life, where the deceased is not present. However, sometimes pathological grief develops, which is reflected as a prolonged grief disorder in the new classifications - The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (Text Revicion) - DSM-5-TR and the 11th International Classification of Diseases ICD-11. Despite the definition of diagnostic criteria for pathological grief and their registration as diagnoses in the latest editions of diagnostic classifications, in studies related to the course of grief, many issues remain that require attention and study in order to ensure effective support for people experiencing loss in a context relevant to Ukraine. The descriptive part of the article, based on literary sources, identifies questions that may arise when studying the topic of grief, and provides an analysis of literary data on factors that may influence the grieving process. The article also presents the results of a study aimed at increasing the effectiveness of assistance to people experiencing the loss of a loved one by identifying the relevance of the topic of loss of a loved one for the population of Ukraine during the war, identifying the readiness of people experiencing grief to seek help, and the need for information to raise awareness of the grieving process both for people experiencing loss and among those who want to support them. Materials and methods: a quantitative online study was conducted involving 400 respondents aged 18 to 55. Results and discussion. According to the survey results, the topic of loss was relevant for Ukrainians; most respondents noted the importance of understanding what happens to a person during the experience of loss, at the same time, seeking help through contacting mental health professionals is not common among people experiencing loss, even in the presence of pronounced manifestations of grief. Conclusions. The relevance of studying the features of grief of Ukrainians experiencing the loss of a loved one during the ongoing war was revealed, as well as the relevance of developing an educational direction on the topic of experiencing loss with a focus on destigmatizing contacting mental health professionals and creating high-quality psychoeducational materials related to the issues of experiencing loss.